Caracterização genética de populações naturais de Palicourea coriacea (Cham) K. Schum utilizando marcadores moleculares - BARBOSA, Taryana Coelho Sales (2006)
The Species Palicourea coriacea (Cham) K,Shum is a species little know, it is belonging to the Rubiaceae family, popularly known as douradinha. The popular use medicine in the therapy of kidneys illnesses. The popular name douradinha is associated with the color of the bracts and of the stem and the species occurs in Cerrado s Bioma, however in different environments. Studies about the genetic diversity and its distribution in natural populations of P. coriacea are of extreme importance for the definition of adequate strategies of handling and cultivation, however they do not exist in literature, studies of this nature. This work had as objective to evaluate the genetic structure from nine natural populations of P. coriacea, collected in States of Goiás and Bahia and to evaluate the genetic diversity of these populations through markers RAPD. The P. coriacea species presented one high level of genetic diversity, or heterozygosity waited by Nei (1972) that it varied between 0,259 and 0,338 in the populations, with equal on average value the 0,296. The AMOVA disclosed that 23% of the total variability is meeting each other between populations. Although the estimates of apparent gene flow (Nm) have disclosed values inferior to one, on the other hand, equal the 0,83. The analyses of Bayesian Statistics had disclosed to a value of f (FIS) equal the 0,98 suggesting the possibility of this species has behavior like autogamous species. The analyses of grouping of the populations using Bayesian and AMOVA statistics disclosed that it does not exist a correlation between geographic distance and genetic distance all the nine populations they grouping, eventually, not obeying its geographic origin. Then, the hypothesis previously formulated of that geographically next populations would be genetic next, was discarded for the results gotten for the Mantel test where it got a correlation of 0,155. In addition, this relatively high inter populations differentiation allows to recommend to a strategy ex situ of the genetic variability using the biggest possible number of populations. In what, the conservation says respect in situ must be taken in account characteristic genetic and demographic of this species considering that this fact implies in the possibility of a continuous evolution and in the development of new adaptable strategies. It is necessary to have conscience on the distribution of the genetic diversity of these areas with intention to not only promote polities for preservation of found natural populations in national parks, but yes to private preservation of the legal reserves and properties.